2011
DOI: 10.21273/hortsci.46.9.1287
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Daily Water Use of Two Petunia Cultivars Based on Plant and Environmental Factors

Abstract: Many ornamental plant growers water excessively to reduce the risk of drought stress. Scheduling irrigation in greenhouses is challenging because there is little quantitative information about ornamental plant water requirements and how water use changes when plants are grown in varying greenhouse environmental conditions. Models to estimate the daily water use (DWU) of greenhouse crops may provide a useful tool to conserve irrigation water. Our objective was to develop a model to predict DWU based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
1
19
0
2
Order By: Relevance
“…This corroborates the findings of van Iersel et al (2010), who observed that daily fluctuations in irrigation demand were strongly correlated with DLI. Kim et al (2011) found that DLI was the most important environmental factor in predicting plant water use and proposed a model for predicting daily water use in greenhouse settings based on plant age and DLI. In that study, other environmental factors such as temperature and vapor pressure deficit improved the model fit less than DLI.…”
Section: Resultsmentioning
confidence: 99%
“…This corroborates the findings of van Iersel et al (2010), who observed that daily fluctuations in irrigation demand were strongly correlated with DLI. Kim et al (2011) found that DLI was the most important environmental factor in predicting plant water use and proposed a model for predicting daily water use in greenhouse settings based on plant age and DLI. In that study, other environmental factors such as temperature and vapor pressure deficit improved the model fit less than DLI.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of incoming radiation and corresponding cooler conditions reduces water use in plants as well. In fact, Kim et al (2011) found that DLI was the most significant correlation with water use. Additionally, Garland et al (2012) found that DLI was strongly correlated to water use in plants, attributable in large part to larger plants and more leaf area in treatments receiving greater DLI.…”
mentioning
confidence: 98%
“…This enables predictive feed-forward management of water use with plant and environmental water-use models. Kim et al (2011) demonstrated that the measured daily plant evapotranspiration of petunia (Petunia ·hybrida) can be precisely modeled in greenhouse production with measurements of crop growth (days after planting, daily light integral, vapor pressure deficit, and air temperature). Kim and van Iersel's empirical modeling approach demonstrates the sensitivity of plant water use to these four easily measured variables.…”
Section: Approachesmentioning
confidence: 99%